2022
DOI: 10.3390/pharmaceutics14061162
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Physiologically Based Pharmacokinetic Model to Predict Cefazolin and Cefuroxime Disposition in Obese Pregnant Women Undergoing Caesarean Section

Abstract: Intravenous (IV) cefuroxime and cefazolin are used prophylactically in caesarean sections (CS). Currently, there are concerns regarding sub-optimal dosing in obese pregnant women compared to lean pregnant women prior to CS. The current study used a physiologically based pharmacokinetic (PBPK) approach to predict cefazolin and cefuroxime pharmacokinetics in obese pregnant women at the time of CS as well as the duration that these drug concentrations remain above a target concentration (2, 4 or 8 µg/mL or µg/g) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…This is consistent with prior evidence that reported suboptimal ertapenem PTA at MICs ≥0.5 mcg/mL in obese patients 55,56 . Moreover, Chambers, et al found that one dose of ertapenem 1 g achieved PTA in bone of ≤45% when the MIC was ≥0.25 mg/L, suggesting obese patients with bone and joint infections are at greatest risk of suboptimal ertapenem dosing (median BMI 37.8 kg/m 2 ) 32–44,57 . This problem may be more pronounced in gram‐positive or mixed infections given differences in MIC breakpoints (CLSI breakpoint for Enterobacterales ≤0.5 mg/L, Streptococci ≤1 mg/L) 28…”
Section: Review Of Specific Antimicrobial Agentssupporting
confidence: 88%
See 3 more Smart Citations
“…This is consistent with prior evidence that reported suboptimal ertapenem PTA at MICs ≥0.5 mcg/mL in obese patients 55,56 . Moreover, Chambers, et al found that one dose of ertapenem 1 g achieved PTA in bone of ≤45% when the MIC was ≥0.25 mg/L, suggesting obese patients with bone and joint infections are at greatest risk of suboptimal ertapenem dosing (median BMI 37.8 kg/m 2 ) 32–44,57 . This problem may be more pronounced in gram‐positive or mixed infections given differences in MIC breakpoints (CLSI breakpoint for Enterobacterales ≤0.5 mg/L, Streptococci ≤1 mg/L) 28…”
Section: Review Of Specific Antimicrobial Agentssupporting
confidence: 88%
“…Additionally, the use of a simple weight cutoff for dose increase may be flawed as it does not account for differences in body size and composition 2 . Small, retrospective, and/or single‐center studies of a variety of surgical procedures continue to emerge and demonstrate conflicting results on adequacy of cefazolin adipose tissue or interstitial fluid concentrations in obesity, despite adequate plasma concentrations 1,14,40–44 …”
Section: Review Of Specific Antimicrobial Agentsmentioning
confidence: 99%
See 2 more Smart Citations
“…This base model for non-pregnant subjects was then extended to predict ceftazidime kinetics in pregnant subjects at different gestational weeks (GWs) by selecting the built-in pregnancy population within the Simulator. The changes in predicted values for GFR ( GFR pred ), CO ( CO pred ), and RBF ( RBF pred ) are described in the PBPK model using the following functions based on a previously published analysis [ 2 ]: where are the baseline values in non-pregnant women [ 2 , 24 , 25 ]. Exposure in the fetus was simulated to occur via linking the maternal PBPK model to the multi-compartment feto-placental model ( Figure 1 ).…”
Section: Methodsmentioning
confidence: 99%